Analisis Marketing Mix 4P untuk Meningkatkan Produktivitas Penjualan pada CV. Ganep Tradisi Solo - Afnita Ardilla, Dea; Wahyu Utami, Indah; Nur Diansari, Brillian (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to analyze the influence of marketing mix strategies (product, price, place, and promotion) on the enhancement of sales productivity at CV. Ganep Tradisi Solo. The research method employed is quantitative with a statistical approach. Data were collected from 52 respondents who are consumers of CV. Ganep Tradisi Solo through Likert-scale questionnaires. Validity, reliability, and classical assumptions tests were conducted to ensure data validity and reliability. Data analysis was performed using multiple linear regression. The results of the analysis indicate that product, price, place, and promotion significantly influence the enhancement of sales productivity. In conclusion, marketing mix strategies have a positive impact on enhancing the sales productivity of CV. Ganep Tradisi Solo's bakery products.